Main Trends in Russian Geopolitics after 1991 (Politeja, 2019)
Russian geopolitical thought after the collapse of the USSR can be classified in different ways. However, it always remains under the influence of the same conditions (the trauma of a historical downfall) and proposes clear indications for the foreign policy of the state. The article presents a preliminary view of some directions in Russian geopolitical thought from the point of view of their origin. The study focuses on seven trends: the visions of Great Russia in a multipolar world order, Neo-Eurasianism, the insular theory, military geopolitics, the thought of political geographers, the geopolitics of the Russian World doctrine with its varieties in the form of information geopolitics and cyber- geopolitics, and, last but not least, geoeconomics. A typological study of contemporary Russian geopolitical thought reveals two developmental tendencies: one aiming at radical and ideological concepts and the other proposing a semi-scientific approach.